Sistem Akreditasi Pemantauan dan Relevansinya Bagi Sekolah Tinggi Teologi dan Sekolah Tinggi Agama Kristen - Markus Oci (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2020)
Abstract. Accreditation is an assessment activity in accordance with established criteria based on the National Higher Education Standards. The legal basis for the monitoring accreditation contained in Permendikbud Number 05 of 2020 besides using the instruments as referred to in Article 10, the Accreditation of Study Programs and Higher Education also uses data and information on the PDDIKTI. In the implementation of monitoring accreditation, it is intended for Study Programs and Universities that already have an Accreditation warning. Reporting quantitative data and information in PDDIKTI as a measurement tool or document in the monitoring process of monitoring accreditation. Quantitative data and information in PDDIKTI include: education and teaching, research, community service. With the enactment of monitoring accreditation brings good news to Universities and Study Programs, where Universities and Study Programs are more focused on the TRI DARMA Higher Education (Education and Teaching, Research, Community Service) activities. For theological colleges and Christian religious colleges, which are routinely reported only in the field of education and teaching while the field of research and community service has never been reported in the PDDIKTI. Not all Theological Colleges and Christian Colleges routinely fill out and report data and information in PDDIKTI every semester and even every Academic Year. This becomes a problem for theological colleges and Christian colleges if they follow monitoring accreditation. The implementation of SPMI which includes: Determination, Implementation, Evaluation, Control and Improvement has not been maximized, there are even some Theological Colleges and Colleges of Christian Religion Colleges and Christian Religious Colleges Study Program have not implemented it.Abstrak. Akreditasi merupakan kegiatan penilaian sesuai dengan kriteria yang telah ditetapkan berdasarkan Standar Nasional Pendidikan Tinggi. Dasar hukum akreditasi pemantauan termaktum dalam Permendikbud Nomor 05 Tahun 2020 selain menggunakan instrumen sebagaimana dimaksud dalam Pasal 10, Akreditasi Program Studi dan Perguruan Tinggi juga menggunakan data dan informasi pada PDDIKTI. Dalam pelaksanaan akreditasi pemantauan diperuntukkan bagi Program Studi dan Perguruan Tinggi yang sudah memiliki peringat Akreditasi. Pelaporan data dan informasi kuantitatif di PDDIKTI sebagi alat ukur atau dokumen dalam proses penilaian akreditasi pemantuan. Data dan informasi kuantitatif di PDDIKTI mencakup: bidang pendidikan dan pengajaran, penelitian, pengabdian kepada kemasyarakat. Dengan diberlakukan akreditasi pemantauan membawa kabar baik bagi Perguruan Tinggi dan Program Studi, dimana Perguruan Tinggi dan Program Studi lebih fokus kepada kegiatan TRI DARMA Perguruan Tinggi (Pendidikan dan Pengajaran, Penelitian, Pengabdian Kepada Masyarakat).Bagi Sekolah Tinggi Teologi dan Sekolah Tinggi Agama Kristen, yang rutin dilaporkan hanya bidang Pendidikan dan Pengajaran sedangkan bidang Penelitian dan Pengabdian Kepada Masyarakat tidak pernah dilaporkan di PDDIKTI. Tidak semua Sekolah Tinggi Teologi dan Sekolah Tinggi Agama Kristen secara rutin mengisi dan melaporkan data dan informasi di PDDIKTI setiap semester bahkan tiap Tahun Ajaran. Hal ini menjadi permasalahan bagi Sekolah Tinggi Teologi dan Sekolah Tinggi Agama Kristen apabila mengikuti akreditasi pemantauan. Pelaksanaan SPMI yang meliputi :Penetapan, Pelaksanaan, Evaluasi, Pengendaliaan dan Peningkatan belum dimaksimalkan, bahkan ada beberapa Sekolah Tinggi Teologi dan Sekolah Tinggi Agama Kristen Perguruan Tinggi dan Program Studi Perguruan Tinggi Keagamaan Kristen belum menerapkannya.